Proceedings of the 10th International Driving Symposium on Human Factors in Driver Assessment, Training and Vehicle Design: Dri 2019
DOI: 10.17077/drivingassessment.1720
|View full text |Cite
|
Sign up to set email alerts
|

The Conspicuity Benefits of Bicycle Taillights in Daylight

Abstract: Bicyclists risk being injured or killed in crashes with motor vehicles, even during the daytime. Therefore, cyclists must help approaching drivers detect and recognize their presence. The present study examined the conspicuity benefits of bicycle taillights during the daytime. Participants' eye movements were recorded as they searched for vulnerable road users in videos recorded from a driver's perspective in a moving vehicle. Five of the videos contained a bicyclist who displayed one of five taillight configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…In other words, taillights that are mounted to the seat post of the bicycle with or without lights on the rider's heels can help observers to recognize the presence of the bicyclist from farther distances. This finding adheres to the results of similar studies that assessed the benefits of taillights on bicyclist daytime and nighttime conspicuity (e.g., Blomberg et al, 1986;Edewaard et al, 2017;Edewaard et al, 2018;Edewaard et al, 2020;Koo & Dunne, 2012;Koo & Huang, 2015;Matthews & Boothby, 1980;Watts, 1984).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…In other words, taillights that are mounted to the seat post of the bicycle with or without lights on the rider's heels can help observers to recognize the presence of the bicyclist from farther distances. This finding adheres to the results of similar studies that assessed the benefits of taillights on bicyclist daytime and nighttime conspicuity (e.g., Blomberg et al, 1986;Edewaard et al, 2017;Edewaard et al, 2018;Edewaard et al, 2020;Koo & Dunne, 2012;Koo & Huang, 2015;Matthews & Boothby, 1980;Watts, 1984).…”
supporting
confidence: 89%
“…This can be interpreted as an encouraging finding because the First Glance, Final Glance Prior to Detection, and Detection distances were each greater than 200 m, which (for a vehicle traveling at 35 mph) would give a driver over 12 seconds to process the visual information corresponding to the bicyclist before they are adjacent to the bicyclist. These results are very similar to the results of the eye tracking experiment conducted by Edewaard et al (2018), which found that the distances from which participants detected a bicyclist displaying the same configurations in daytime videos of drive-bys of a bicyclist were not significantly different from each other.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Bicycle taillights can help observers to recognize bicyclists more easily and from farther distances during the daytime (Edewaard et al, 2019;Edewaard et al, 2018). While taillights are conventionally mounted to the seat post, taillights have the potential to be more effective when mounted elsewhere on the bicycle or rider.…”
mentioning
confidence: 99%